Heat transfer in cylindrical and tappered bar [mikrofilem] - 315178 Muhamad Suyot Kadir (Fakulti Kejuruteraan Jentera : UTM, 1978)
Thesis (Bachelor of Mechanical Engineering) - Universiti Teknologi Malaysia, 1978